Anticoagulation for coexisting bioprosthetic aortic valve thrombosis and anticoagulant‐related bleeding: "A double edge sword". Issue 10 (23rd September 2020) - Xu, Jiaqian; Lata, Adrian L.; Zhou, Li; Upadhya, Bharathi; Pu, Min
Abstract: The choice of anticoagulant agents for newly implanted bioprosthetic valve varies significantly, particularly in the presence of postoperative atrial fibrillation with increasing use of nonvitamin K oral anticoagulation (NOACs) in recent years. We reported a challenging case with a coexisting bioprosthetic aortic valve thrombosis and significant anticoagulant‐related bleeding. Clinical management strategy and brief literature review were presented.